11-Element Yagi Antenna for 1800 MHz Frequency - Fannia Rekha hamdila; Nasrul Nawi; Sri Nita; M Noer; Herman Yani (Politeknik Negeri Padang, 2024)
The need for internet connection is very important because everything is connected to each other with the internet, but due to limitations on access points, many areas are still experiencing difficulties in accessing the internet, one of which is the suburban area. Suburban areas that are indicated to be still difficult to reach due to obstacles from buildings, and the influence of weather. In order for the signal to be reached in this area, an 11-element yagi antenna with a working frequency of 1800 MHz is needed which is expected to produce a high gain so that the antenna beam is maximised. This final project aims to design an 11-element Yagi antenna at a working frequency of 1800 MHz, and analyse antenna parameters such as return loss, VSWR, bandwidth, gain, and polaradiation. Where the design of the yagi antenna uses CST Studio Suite 2019 software. After the simulation results are as desired, then fabrication or manufacture of the antenna is carried out. The simulation results after optimising are -26.00 dB, VSWR 1.10, and gain 12.32 dB. After the simulation is carried out, the next fabrication or manufacture of the 11-element Yagi antenna, the measurement obtains a return loss value of -11.29 dB, and VSWR 1.74, although the measurement results are far from the simulation but the results of this measurement have met the requirements of the antenna specifications.